2014
DOI: 10.1007/s00213-014-3645-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of yokukansan in treatment-resistant schizophrenia: a randomized, double-blind, placebo-controlled trial (a Positive and Negative Syndrome Scale, five-factor analysis)

Abstract: The results of the present study indicate YKS to be a potential adjunctive treatment strategy for treatment-resistant schizophrenia, particularly to improve excitement/hostility symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Yokukansan has been used to treat various diseases such as Alzheimer's disease and schizophrenia [6][7][8][9][10]. However, whether or not yokukansan is able to reduce demyelination in the CNS remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yokukansan has been used to treat various diseases such as Alzheimer's disease and schizophrenia [6][7][8][9][10]. However, whether or not yokukansan is able to reduce demyelination in the CNS remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines and pro-oxidant molecules cause irreversible damage in demyelination in the CNS [2,4]. It is possible that yokukansan reduces these inflammatory responses without serious adverse effects [6][7][8][9][10]. Moreover, yokukansan might also promote maturation of oligodendrocytes during the remyelination phase [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of enrolled participants was 1725 among the 14 included studies (868 participants in the treatment group and 857 in the control group) 17 – 30 , there were no observed significant differences in terms of gender, age and other demographic information. One study included Japanese patients 18 while the remaining research subjects were all Chinese. Regarding specific selection of the treatment periods, one study reported changes after 16 weeks 25 , 8 studies were limited to 12 weeks 19 , 21 , 23 , 26 – 30 , 4 studies were limited to 8 weeks 17 , 20 , 22 , 24 and one study only identified changes after 4 weeks 18 .…”
Section: Resultsmentioning
confidence: 99%
“…In that book, it is suggested to give yokukansan to both mothers and children simultaneously to treat night crying. Currently, yokukansan is widely prescribed for a wide age range in Japan because of its potent effects on the symptoms of a variety of important disorders such as neurosis, insomnia, dementia, schizophrenia, and post‐partum depression (PPD) .…”
Section: Introductionmentioning
confidence: 99%